Foucault, neoliberalism, and beyond - Sawyer, Stephen W., 1974- (Rowman & Littlefield International, 2019)
Offers a comprehensive account of Foucault's relationship to neoliberalism that is driven not by polemics but a careful reading of Foucault's texts and political positions.